Investment Process in China's Mutual Funds and Application of Artificial Intelligence - Xie, Ningjia (2008)
This paper explored the process of investment management in both theory and practice in China's mutual fund industry and reviewed the applications of artificial intelligence including Rule-based Expert Systems, Genetic Algorithms, Artificial Neural Network, and Support Vector Machines in financial forecasting, asset allocation and stocks selection.